Using Radiogenic Noble Gas Nuclides to Identify and Characterize Rock Fracturing - W. Payton Gardner; Stephen J. Bauer; William M. Kibikas; Brynna Siluk; Scott Broome; Chris Strickland; Christine Johnson; Vince Vermeul (Earth and Space Science)
Abstract Fracture‐released radiogenic noble gas nuclides are used to identify locations and constrain the volume of new fracture creation during subsurface detonations. Real‐time, in situ noble gases and reactive gases were monitored using a field‐deployed mass spectrometer and automated sampling system in a multilevel borehole array. Released gases were measured after two different detonations having distinct energy, pressure, and gas volume characteristics. Explosive‐derived gases (N2O, CO2) and excess radiogenic 4He and 40Ar above atmospheric background are used to identify locations of gas transport and new fracture creation after each detonation. Fracture‐released radiogenic 4He is used to constrain the volume of newly created fractures with a model of helium release from fracturing. Explosive by‐product gas was observed in multiple locations both near and distal to the shot locations for both detonations. Radiogenic 4He and 40Ar release from rock damage was observed in locations near the detonation after the second, more powerful detonation. Observed 4He response is consistent with a model of diffusive release from newly created fractures. Volume of new fractures estimated from the 4He release ranges from 1 to 5 m2 with apertures ranging from 0.1 to 1 μm. Our results provide evidence that radiogenic noble gases released during fracture creation can be identified at the field scale in real time and used to identify timing and location of fracture creation during deformation events. This technique could be useful in subsurface science and engineering problems where the location and amount of newly created rock fracturing is of interest including fault rupture, mine safety, subsurface detonation monitoring and reservoir stimulation.